Eksplorasi Pengalaman Mahasiswa Magang Dalam Mengelola Proposal dan LPJ di Biro Kesejahteraan Rakyat Kantor Gubernur Sumatera Utara - Dinda Wulandari; Ilda Safitri; Intan Camelia; Septi Fatma Khairan; Syairal Fahmy Dalimunthe (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to explore the experience of interns in managing proposals and accountability reports (LPJ) at the Welfare Bureau of the North Sumatra Governor's Office. The method used in this study is qualitative research with a case study approach. The result of this research is the process of managing the incoming proposal file and accountability sheet by following the rules that apply to the Administration Sub-Division, People's Welfare Bureau of the North Sumatra Governor's Office. The management of proposals and accountability reports starts from the input process, printing the disposition sheet, to numbering the files, all carried out based on the directions given.